Iran´s dilemma: looking back to see forward - Balla, Evanthia (2015)
Over two decades after the end of the Cold War, Iran and the West continue struggling to find their way out of their cold relationship. Iran is the world’s fourth-largest oil producer, holding 12,7% of OPEC reserves and the second-largest holder of natural gas reserves. Yet, Iran although a powerful regional player is a country governed by a repressive theocratic regime, developing an unpredictable nuclear programme, accusing the West, and especially the United States of America, for a world order of fear and domination.